140k views
5 votes
Can you help me with this !!

Can you help me with this !!-example-1
User Doynax
by
6.2k points

1 Answer

2 votes

Answer:

(0, 2)

Explanation:

Substitution would be a good way of solving these simultaneous equations. Replace the 'x' in the second equation by ' -y + 2, ' which comes from the first equation. Then we have:

3y + (-y + 2) = 6.

Simplifying this, we get:

3y - y + 2 = 6, or

2y = 4,

or y = 2.

Now let's find x by substituting 2 for y in the first equation:

x = -(2) + 2 = 0. So x = 0.

The solution is the point (0, 2). Note that the second equation is true if we let x = 0 and y = 2.

User Sarfaraz Khan
by
5.5k points